Characterization of peripheral cytokine-secreting cells responses in HIV/TB co-infection - Tan, Yuting; Guo, Wei; Zhu, Qi; Song, Shihui; Xiang, Yanni; Wu, Songjie; Zou, Shi; Yan, Yajun; Feng, Ling; Luo, Mingqi; Shen, Ling; Feng, Yong; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Currently the responses of peripheral cytokines-secreting cells in the natural course of human immunodeficiency virus (HIV) and tuberculosis (TB) co-infection haven’t been fully elucidated. Methods: The function of peripheral proinflammatory, regulatory and cytotoxic cytokines-secreting cells were investigated by direct intracellular cytokine staining (ICS) and flow cytometry, and meanwhile, the absolute numbers of different cytokines-secreting cells were measured among patients with HIV/TB co-infection (HT group), and compared with healthy controls (HC group), patients with TB (TB group) and patients with HIV infection (HIV group). After one week’s anti-TB treatment, the changes of percentages of cytokines-secreting cells were further evaluated in TB and HT groups. Results: Totally 26 individuals in HC group, 51 in TB group, 26 in HIV group and 29 in HT group were enrolled. HT group had significantly lower absolute numbers of IFN-γ+CD4+, IFN-γ+CD8+, TNF-α+CD4+, IL17A+CD4+ T cells and TNF-α+CD14+ monocytes than TB and HIV groups. Compared with TB group, the percentages of CD8+ T cells secreting IFN-γ and perforin (p=0.010; p=0.043) were significantly lower among HT group. Compared with HIV group, the percentages of CD4+, CD8+ T cells and CD14+ monocytes secreting TNF-α (p=0.013; p=0.001; p<0.001) were significantly decreased, and the percentage of CD8+ T cells secreting IL-17A (p=0.015) was significantly increased among HT group. Both the percentages of CD4+ T cells secreting TGF- (p<0.001; p=0.001), and CD4+ and CD8+ T cells secreting granzyme A (all p<0.001), were significantly higher among HT group than among TB group and HIV group. After one week’s anti-TB treatment, an increased percentage of CD4+ T cells secreting TNF-α (p=0.003) was found in TB group, and an increased percentage of CD8+ T cells secreting TNF-α (p=0.029) was found in HT group. Conclusion: Significantly different functional profiles of peripheral proinflammatory, regulatory, and cytotoxic cytokines-secreting cells were observed in the natural course of HIV/TB co-infection compared to TB and HIV infection alone, even though the absolute numbers of those cells were significantly lower in HIV/TB co-infection. TNF-α-secreting CD8+ T cells may be a more sensitive marker for early evaluation of anti-TB treatment efficacy in patients with HIV/TB co-infection.